Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHB-HV) impregnated with mango leaves extracts using supercritical solvent impregnation - Ludisbel León-Marcos; Antonio Montes; Diego Valor; Ignacio García-Casas; Noelia D. Machado; Clara Pereyra (Journal of CO2 Utilization)
The impregnation of the polymer poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHB-HV) with mango leaves extract (MLE) was carried out using the Supercritical Solvent Impregnation method. The impregnation loads, antioxidant compounds and physical properties of impregnated polymers were investigated with the variation of operating parameters (temperature (35 and 55 °C), pressure (10, 20 and 30 MPa) and depressurization rate (0.1 and 5 MPa/min)). Furthermore, the influence of varying impregnation times (1, 3, 6, 10, 24 h) with 30 MPa, 35 °C and 5 MPa/min was also investigated and the antimicrobial capacity (AC) was determined. The results showed a decrease of the impregnation loads, antioxidant and antimicrobial capacities with increasing impregnation time. At 30 MPa, 35 ºC and 5 MPa/min with an impregnation time of 1 h, impregnation loads and antioxidant capacities of 2.82 ± 0.04 mg MLE/100 mg PHB-HV and 2.77 ± 0.10 mg AC/100 mg PHB-HV, respectively, and a growth inhibition percentage against Staphylococcus aureus and Escherichia coli bacteria greater than 60 % were obtained.